2015
DOI: 10.1109/jstars.2015.2403877
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Heat Content and Mean Temperature of Different Ocean Layers

Abstract: Oceans are reservoirs of heat energy represented by the heat content or the mean temperature, and are the source of energy for the atmospheric processes. Which process of the atmosphere interacts with the energy of which layer of the ocean is not clear, primarily, because of the nonavailability of oceanic heat energy of different layers on a required temporal and spatial scales. Realizing this requirement, we compute the ocean heat content (OHC) and the ocean mean temperature (OMT) from surface to 50, 100, 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…as one unit. The National Remote Sensing Centre (NRSC) computed the OHC and ocean mean temperature from surface to 50 m, 100 m, 150 m, 200 m, 300 m, 500 m, 700 m and up to 26 • C isotherm depth (i.e., TCHP) following Jagadeesh et al [15]; the data isavailable on the NRSC website, Bhuvan (http://bhuvan.nrsc.gov.in). They used the artificial neural network (ANN) technique to estimate the above parameters from SST, sea surface height anomaly, and climatological OHC values at the respective depths.…”
Section: Methodsmentioning
confidence: 99%
“…as one unit. The National Remote Sensing Centre (NRSC) computed the OHC and ocean mean temperature from surface to 50 m, 100 m, 150 m, 200 m, 300 m, 500 m, 700 m and up to 26 • C isotherm depth (i.e., TCHP) following Jagadeesh et al [15]; the data isavailable on the NRSC website, Bhuvan (http://bhuvan.nrsc.gov.in). They used the artificial neural network (ANN) technique to estimate the above parameters from SST, sea surface height anomaly, and climatological OHC values at the respective depths.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly in recent years, machine learning has proven to be a cutting-edge application of empirical statistical methods to this field [18]. Of these techniques, neural networks (NN), as one of the most fundamental models of machine learning, has a proven ability to estimate various ocean parameters and subsurface information [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies have demonstrated that, using a variety of machine-learning approaches including artificial neural networks (ANN), surface remote sensing data can be successfully applied to retrieving STA. These studies were inspired by the works of Jagadeesh et al [23] and Guinehut et al [24], which demonstrated that the subsurface thermal structure is dynamically linked to SSH and therefore, can be retrieved from remote sensing data. Su et al [14] verified the credibility of this theory by combining remote sensing data with machine-learning techniques such as support vector machines and random forests.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations